Implementasi Terapi Relaksasi Otot Progresif Pada Klien Skizofrenia Dengan Masalah Halusinasi Pendengaran - Marta Pastari; Sri Martini; Latifa Nursyakbani; Ari Athiutama (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: Schizophrenia is a severe mental disorder that is frequently accompanied by auditory hallucinations, which may interfere with patients’ concentration, behavior, and social interaction. Effective nursing interventions are therefore needed to help patients manage these symptoms. One such intervention is progressive muscle relaxation therapy, a technique designed to reduce physical tension and psychological stress, thereby promoting calmness and improving patients’ ability to control hallucinations. Objective: This study aimed to describe the implementation of progressive muscle relaxation therapy in patients with schizophrenia experiencing auditory hallucinations. Methods: A descriptive case study design was employed involving four female patients who met the inclusion criteria of being cooperative, willing to participate, and physically healthy. Data were collected using assessment forms, observation checklists, standard operating procedures, leaflets, and informed consent forms. The intervention was administered for 5 days, with each session lasting 10–15 minutes, while patient progress was observed over 7 days. Data were obtained through interviews and observations and were presented in the form of nursing care documentation. Results: The findings showed a reduction in the signs and symptoms of auditory hallucinations in all patients after the intervention. The percentage of signs and symptoms decreased from 100% to 12.5% in patient A, from 75% to 12.5% in patient M, from 100% to 25% in patient R, and from 75% to 25% in patient H. In addition, all patients reported feeling calmer and more able to control their hallucinations when the voices reappeared. Conclusion: In conclusion, progressive muscle relaxation therapy may help reduce the signs and symptoms of auditory hallucinations in patients with schizophrenia. This intervention may serve as a simple, safe, and practical psychiatric nursing strategy to support hallucination management.